Neighbourhood food and physical activity environments in England, UK: does ethnic density matter? - Molaodi Oarabile R; Leyland Alastair H; Ellaway Anne; Kearns Ade; Harding Seeromanie (BMC, 2012)
Abstract Background In England, obesity is more common in some ethnic minority groups than in Whites. This study examines the relationship between ethnic concentration and access to fast food outlets, supermarkets and physical activity facilities. Methods Data on ethnic concentration, fast food outlets, supermarkets and physical activity facilities were obtained at the lower super output area (LSOA) (population average of 1500). Poisson multilevel modelling was used to examine the association between own ethnic concentration and facilities, adjusted for area deprivation, urbanicity, population size and clustering of LSOAs within local authority areas. Results There was a higher proportion of ethnic minorities residing in areas classified as most deprived. Fast food outlets and supermarkets were more common and outdoor physical activity facilities were less common in most than least deprived areas. A gradient was not observed for the relationship between indoor physical activity facilities and area deprivation quintiles. In contrast to White British, increasing ethnic minority concentration was associated with increasing rates of fast food outlets. Rate ratios comparing rates of fast food outlets in high with those in low level of ethnic concentration ranged between 1.28, 95% confidence interval 1.06-1.55 (Bangladeshi) and 2.62, 1.46-4.70 (Chinese). Similar to White British, however, increasing ethnic minority concentration was associated with increasing rate of supermarkets and indoor physical activity facilities. Outdoor physical activity facilities were less likely to be in high than low ethnic concentration areas for some minority groups. Conclusions Overall, ethnic minority concentration was associated with a mixture of both advantages and disadvantages in the provision of food outlets and physical activity facilities. These issues might contribute to ethnic differences in food choices and engagement in physical activity.